2022
DOI: 10.1149/10701.7131ecst
|View full text |Cite
|
Sign up to set email alerts
|

The Household Financial Management during the Covid Pandemic – a Comparative Analysis

Abstract: Purpose: to understand and personal financial management before and during the Covid Pandemic and its impact. Further, to make certain suggestions to better personal and household financial management. Methodology: This study was survey based, 192 respondents were picked from Government, private, business, self-employees and others. Paired t-test was applied to know whether the mean difference between financial behavior of individuals before and during the pandemic along with required descriptive statistics. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A study performed by Gade, Goli and Ratnaker (2021) in India investigated the financial behaviour of households before and during the COVID-19 pandemic. The respondents were required to state what percentage of income they used to spend before the COVID-19 pandemic and during the pandemic on several aspects such as health, education, basic needs, insurance, credit card payments and savings.…”
Section: Pandemic Implications On Financial Behaviour and Related Rel...mentioning
confidence: 99%
See 2 more Smart Citations
“…A study performed by Gade, Goli and Ratnaker (2021) in India investigated the financial behaviour of households before and during the COVID-19 pandemic. The respondents were required to state what percentage of income they used to spend before the COVID-19 pandemic and during the pandemic on several aspects such as health, education, basic needs, insurance, credit card payments and savings.…”
Section: Pandemic Implications On Financial Behaviour and Related Rel...mentioning
confidence: 99%
“…Of this 72%, 33% of respondents are aged 40 and younger. This might be because the respondents had a experience similar to the respondents from the study of Gade et al (2021) during the COVID-19 pandemic, where it was identified that the savings of respondents were not sufficient to protect them during the COVID-19 pandemic.…”
Section: Budgetsmentioning
confidence: 99%
See 1 more Smart Citation